Twitter Sebagai Media Speak Up Perempuan Dalam Kasus Pelecehan Seksual - Marundha, Ainy Sucianti; Rahmiputri, Aisha Andari; Fatina, Nadiah Nur; Hasna, Safira; Seyma, Qoryna Noer (Program Fakultas Dakwah dan Ilmu Komunikasi (FDIKOM), UIN Syarif Hidayatullah Jakarta, 2022)
Sexual harassment is not something that has just been heard or recently talked about. Sexual harassment is still a threat and taboo to be discussed and is not an easy thing to get rid of. This often happens to women in Indonesia, both in public places and on social media. However, along with the presence of social media, women can take advantage of the forum as a place where they express their opinions to voice issues of empowering women. Therefore, the objective of this research is to find out women victims of sexual harassment in utilizing social media Twitter as a forum for expression related to sexual harassment cases. This research used theory of feminism, cyberfeminism, sexual harassment and the relation between technology and women. This research used qualitative approach and constructivism strategy. The data was collected through in-depth interview with female victims of sexual harassment who dare to speak up on Twitter social media.